2022
DOI: 10.3389/fimmu.2022.865772
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NLRP3 Inflammasome With Nrf2 Inducers in Central Nervous System Disorders

Abstract: The NLRP3 inflammasome is an intracellular multiprotein complex that plays an essential role in the innate immune system by identifying and eliminating a plethora of endogenous and exogenous threats to the host. Upon activation of the NLRP3 complex, pro-inflammatory cytokines are processed and released. Furthermore, activation of the NLRP3 inflammasome complex can induce pyroptotic cell death, thereby propagating the inflammatory response. The aberrant activity and detrimental effects of NLRP3 inflammasome act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 201 publications
(212 reference statements)
0
18
0
Order By: Relevance
“…Previous studies revealed that excessive ROS generation is associated with endoplasmic reticulum (ER) stress, which induces inflammatory response by activating the nuclear factor-kappa B (NF-κB) signaling pathway [34]. Oxidative stress is involved in the activation of NLRP3 inflammatory corpuscles, which is an important component of innate immunity involved in the process of inflammatory diseases of the CNS [35][36][37]. Latest studies have shown that NLRP3 is up-regulated in both neuropathic and inflammatory pain models, the activation of which, is also involved in the occurrence and maintenance of postoperative pain [38].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that excessive ROS generation is associated with endoplasmic reticulum (ER) stress, which induces inflammatory response by activating the nuclear factor-kappa B (NF-κB) signaling pathway [34]. Oxidative stress is involved in the activation of NLRP3 inflammatory corpuscles, which is an important component of innate immunity involved in the process of inflammatory diseases of the CNS [35][36][37]. Latest studies have shown that NLRP3 is up-regulated in both neuropathic and inflammatory pain models, the activation of which, is also involved in the occurrence and maintenance of postoperative pain [38].…”
Section: Discussionmentioning
confidence: 99%
“…Upon recognition of PAMPs or host-derived DAMPs, signals are transmitted to the immune system to initiate inflammation. Inflammasome promotes the maturation and secretion of pro-IL1β and pro-IL18 to produce IL-1β and IL-18 by causing the shearing and activation of Caspase-1 during the natural immune defense (Tastan et al, 2022). Several inflammasosomes have been identified, including NLRP1, NLRP3, NLRC4, and AIM2 (Cox et al, 2015;Friker et al, 2020).…”
Section: Microglia-associated Inflammasome and Alzheimer's Diseasementioning
confidence: 99%
“…The canonical pathway requires a priming step in the context of low intracellular levels of pro-inflammatory cytokines and NLRP3 that are insufficient to activate the inflammasome complex. The priming step is initiated via TLR4 receptors and leads to nuclear translocation of NFκB, resulting in the transcription of pro-inflammatory cytokines genes [201]. In the activation step, sensor proteins such as NLRP3, recognize various danger signals and interact with ASC via its PYD domain.…”
Section: Ros-mediated Modulation Of the Inflammasomementioning
confidence: 99%